Overview of dietary assessment methods for measuring intakes of foods, beverages, and dietary supplements in research studies - Bailey, Regan L (Current opinion in biotechnology, 2021)
Measuring the dietary intakes of individuals for research and monitoring purposes is notoriously challenging and is subject to both random and systematic measurement error. In this review, the strengths and limitations of current methods to assess dietary and supplemental exposures are described. Traditional methods of dietary assessment include food records, food frequency questionnaires, 24-hour recalls, and screening tools; digital and mobile methods that leverage technology are available for these traditional methods. Ultimately, the choice of assessment method is dependent upon the research question, the study design, sample characteristics, and the size of the sample, to name just a few. Despite their challenges, dietary assessment tools are an important dimension of nutrition research and monitoring.